2022
DOI: 10.3390/math10132345
|View full text |Cite
|
Sign up to set email alerts
|

How Do Pre-/In-Service Mathematics Teachers Reason for or against the Use of Digital Technology in Teaching?

Abstract: The role and the availability of digital technology in society is growing, which is why educators need to increasingly more often decide which types of digital technology to integrate into their teaching and when to integrate them. Thus, those decision-making skills need to be developed and measured especially for pre-service mathematics teachers. Therefore, we conducted an explorative interview study to understand the portfolio of argumentation on whether to use digital technology in different teaching phases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Teacher candidates' training is noteworthy in terms of developing knowledge and skills for DTs (Gonscherowski & Rott, 2022). In this context, it has been concluded that undergraduate education teacher candidates support their use of technology in terms of pedagogical, content, and technology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Teacher candidates' training is noteworthy in terms of developing knowledge and skills for DTs (Gonscherowski & Rott, 2022). In this context, it has been concluded that undergraduate education teacher candidates support their use of technology in terms of pedagogical, content, and technology.…”
Section: Discussionmentioning
confidence: 99%
“…When the use of DTs before undergraduate education is examined, although the views on learning are close to the views on teaching, the views on teaching in the use of DTs after undergraduate education are almost four times higher than the views on learning. It is important to train pre-service teachers for DTs and to develop their "digital technology selection" skills (Gonscherowski & Rott, 2022). This is an indication that undergraduate education has a positive effect on the use of technology by EMTCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted in developing countries in other parts of Africa have explored the general usage of educational technologies and investigated the level of skills possessed by preservice mathematics teachers regarding the integration of digital technologies (Kafyulilo, Fisser, Pieters, & Voogt, 2015;Gonscherowski & Rott, 2022;Njiku, Mutarutinya, & Maniraho, 2022). Some studies have focused on preservice teachers' self-efficacy in technology integration and the factors that hinder them from being able to integrate these technologies into their teaching (Batane & Ngwako, 2017;Olugbara & Letseka, 2020).…”
Section: Problem Statementmentioning
confidence: 99%